Ahmad Ghazali"s Satan - Elmi, Ghorban (HTS teologiese studies, 2019)
This article studies Ghazali’s viewpoint regarding Satan or Iblis. Ghazali’s interpretation of Satan is very different from that of traditional ones. Despite the Koran’s negative portrayal of Satan, Ghazali elaborates a new transformative theology of Satan. He defends Satan and considers him as the paragon of lovers in self-sacrifice. According to him, Satan’s refusal to bow down before God’s creation, Adam, signifies that Satan alone manifests the purest devotion to God’s oneness and is thus the unrivalled champion of tawhid. Ghazali’s sympathetic understanding of Satan is a logical outcome of his theory of love. He depicts Satan not only as a sincere worshipper, but also as a true lover. He loves God even though he curses and casts him out. Because of being cursed, he has acquired a long life and a position of power over the whole world.